2010
DOI: 10.1089/neu.2009.1245
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Hypoxia Exacerbates Brain Tissue Damage: Analysis of Axonal Injury and Glial Responses

Abstract: Traumatic brain injury (TBI) resulting in poor neurological outcome is predominantly associated with diffuse brain damage and secondary hypoxic insults. Post-traumatic hypoxia is known to exacerbate primary brain injury; however, the underlying pathological mechanisms require further elucidation. Using a rat model of diffuse traumatic axonal injury (TAI) followed by a post-traumatic hypoxic insult, we characterized axonal pathology, macrophage/microglia accumulation, and astrocyte responses over 14 days. Rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
99
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(117 citation statements)
references
References 97 publications
10
99
1
Order By: Relevance
“…These results are consistent with other studies that showed astrocytosis peaking between 10 and 14 days following concussion in rodents. 42,49,50 This increase in gliosis is also believed to coincide with macrophage accumulation, which has also been shown to peak at 10 days post-injury. Our data demonstrate that repetitive, noninvasive mTBI in the mouse resulted in a graded injury response, with the extent of reactive astrocytosis increased in animals exposed to repetitive impacts.…”
Section: Discussionmentioning
confidence: 97%
“…These results are consistent with other studies that showed astrocytosis peaking between 10 and 14 days following concussion in rodents. 42,49,50 This increase in gliosis is also believed to coincide with macrophage accumulation, which has also been shown to peak at 10 days post-injury. Our data demonstrate that repetitive, noninvasive mTBI in the mouse resulted in a graded injury response, with the extent of reactive astrocytosis increased in animals exposed to repetitive impacts.…”
Section: Discussionmentioning
confidence: 97%
“…These groups were matched for age. The time a patient spent in the DOC at the day of scanning was used as a covariate (the natural logarithm of the time spent in DOC in days was used; the natural logarithm was chosen, as, given known biological secondary responses to primary brain injury [33,[60][61][62], the effect of time on structural brain injury was expected to be strongest in the initial weeks). The structural brain injury correlating to this covariate was examined.…”
Section: Discussionmentioning
confidence: 99%
“…As the amount of axotomy is commonly used to evaluate the magnitude of diffuse TBI, 31,32 we first analyzed the number of inured axons, visualized via APP accumulation within axonal swellings, 6 hours after TBI (sham n ¼ 2 animals, TBI n ¼ 4, TBI þ ICP elevation n ¼ 5). In accordance with the previous reports, no APP þ axonal swellings were seen in sham-injured controls ( Figure 3A), whereas TBI alone and TBI þ ICP-elevation showed numerous APP þ swellings within layers V and VI of the somatosensory cortex (Figure 3) Figures 3B and 3C).…”
Section: Neuronal Membrane Perturbation But Not Axonal Injury Is Exmentioning
confidence: 99%